The COVID-19 pandemic and lockdowns impacted the sleep and performance of rowers and triathletes - Filice, P. (University of Victoria, 2022)
In early 2020, many businesses (including gyms) were instructed to shut down for an unspecified period of time as a response to the SARS-CoV-2 virus (Casagrande et al., 2020, p.1; Erskine, M., 2020, para.1; O`Brien, 2020, Gyms and Health Centers section, para.1-16). As a result, many people experienced a change in how much they exercised and the quality and quantity of their sleep (Antunes et al., 2020, pp.3,5; Bigalke et al., 2020, p.7; Cellini et al., 2021, pp.113- 115, 117; Constandt et al., 2020, p.4; Pérez-Carbonell et al., 2020, pp.164, 166; Puccinelli et al., 2021, p.6). There was also an increase in the levels of negative mental states, such as anxiety and depression in various populations (Daly et al., 2020, pp.2-5). This study primarily explored changes in exercise and sleep (quality and quantity) as a result of the pandemic in a highly athletic adult population of rowers and triathletes. The data collected from the study also touched upon the changes in the mental states of the participants. A survey was sent across Canada to rowing and triathlon clubs from SurveyMonkey that had both qualitative and quantitative questions to examine these areas of contention. A majority of participants indicated that their sleep quality had worsened as a result the COVID-19 pandemic. However, there wasn`t enough evidence to indicate that the pandemic affected the length of their sleep. The athletic performance of the athletes, as measured by self-report, decreased during the pandemic in an overwhelming number of participants. Finally, although there were many indications of worsened mental health states (such as reports of increased anxiety), there wasn`t a validated questionnaire used to measure changes in mental health concerns in the population related to the COVID-19 pandemic. Some mental health concerns that were shared by the participants indicated other causes than only the pandemic. Future research should include more objective measures of sleep duration and anxiety and depression scores to better clarify those hypotheses.